Kecukupan Modal dan Ukuran Bank: Faktor Pendorong Kinerja Keuangan pada Sektor Perbankan Syariah di Indonesia - Syah, Toufan Aldian (Profit : Jurnal Inovasi Ekonomi dan Bisnis, 2023)
In the era of globalization and advances in information technology, the banking industry faces a series of challenges and opportunities. Financial performance is crucial for banks to remain competitive. This research focuses on two leading financial performance indicators, namely Return on Assets (ROA) and Return on Equity (ROE), as well as how the Capital Adequacy Ratio (CAR) and bank size influence them. Using the Generalized Method of Moments (GMM) method to analyze data from various Islamic banks in Indonesia, this research finds that high CAR and large bank size positively correlate with better financial performance. Although many studies have explored the relationship between CAR and financial performance, the results often vary. Therefore, this study fills the gap in the literature by combining the influence of CAR and bank size on ROA and ROE. The results of this analysis are expected to provide new insights for banking stakeholders regarding the factors that influence financial performance in the Sharia banking sector.